Security designs for the cloud, IoT, and social networking - Le, Dac-Nhuong 1983-; Bhatt, Chintan M. 1988-; Madhukar, Mani (John Wiley & Sons, Inc., 2019)
"Security concerns around the rapid growth and variety of devices that are controlled and managed over the Internet is an immediate potential threat to all who own or use them. This book examines the issues surrounding these problems, vulnerabilities, what can be done to solve the problems, investigating the roots of the problems and how programming and attention to good security practice can combat the threats today that are a result of lax security processes on the Internet of Things, cloud computing and social media"--
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Cloud computing -- Security measures; Internet of things -- Security measures; Social media -- Security measures; Infonuagique; Sécurité; Mesures; Internet des objets; Sécurité; Mesures; Médias sociaux; Sécurité; Mesures; Cloud computing; Security measures